STRATEGI PENINGKATAN PRODUKTIFITAS PERIKANAN TANGKAP SKALA KECIL YANG BERKELANJUTAN DI KABUPATEN ACEH JAYA PROVINSI ACEH - Teuku Amarullah (Universitas Teuku Umar, 2017)
The research is about strategy of productivity improvement of sustainable small-scale capture fisheries in Aceh Jaya, Aceh Province. The research have been conducted four months and it’s start in August 2014 to December 2014. The study aims to determine factors that affecting productifity of sustainable small-scale capture fisheries and strategies for improving productivity of sustainable small-scale capture fisheries in Aceh Jaya, Aceh Province. The Survey method was used for the study. In addition this study is using deep interview to respondents. Data analysis is using linear regression analysis, descriptive analysis and SWOT analysis. The Result show productivity of small-scale capture fisheries in Aceh Jaya was affected number of fishing trips and capital. Type of fishing fleet, fishing equipment, fisherman and fishing experience have not siggnificantly affect the productivity of small-scale capture fisheries. Productivity can be improved by regulation of fisheries department like fishing grounds category, prohibition of fishing is using explosives (fish bomb), trawl, toxin. In addition, improvement of small-scale fisheries can be reached with increasing fisheries extension and economic empowerment of coastal communities and also the strengthening of customary management system (Panglima Laot).